2010
DOI: 10.1179/002032010x12759166444887
|View full text |Cite
|
Sign up to set email alerts
|

Strength properties of selected Uganda timbers

Abstract: To improve the utilisation of timber in building construction and enhance the market value of Ugandan timber species, especially the lesser known, strength properties of 17 species were studied. Small clear specimen tests were conducted in bending, compression and shear parallel to grain using the standard procedures of the American Society for Testing and Materials, ISO 8905:1988, AS/NZS 2878 and BS 373:1957. Results showed significant differences in strength properties of the investigated timbers. A positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The mean values of basic density, compressive strength parallel to grain, MOE, and MOR the whole trees were 0.43 g cm -3 , 42.4 MPa, 8.92 GPa, and 97.3 MPa for A. mangium, 0.33 g cm -3 , 30.6 MPa, 6.84 GPa, and 72.7 MPa for M. eminii, and 0.44 g cm -3 , 39.7 MPa, 8.36 GPa, and 90.3 MPa for M. azedarach (Table 3). With a few exceptions, the mean values of wood properties obtained in the present study were in the range of the values reported by previous researchers (Table 4, Chowdhury et al 2009;Zziwa et al 2010;Makino et al 2012;Jusoh et al 2014;Duong and Matsumura 2018a, b;Duong et al 2019).…”
Section: Wood Propertiessupporting
confidence: 82%
See 1 more Smart Citation
“…The mean values of basic density, compressive strength parallel to grain, MOE, and MOR the whole trees were 0.43 g cm -3 , 42.4 MPa, 8.92 GPa, and 97.3 MPa for A. mangium, 0.33 g cm -3 , 30.6 MPa, 6.84 GPa, and 72.7 MPa for M. eminii, and 0.44 g cm -3 , 39.7 MPa, 8.36 GPa, and 90.3 MPa for M. azedarach (Table 3). With a few exceptions, the mean values of wood properties obtained in the present study were in the range of the values reported by previous researchers (Table 4, Chowdhury et al 2009;Zziwa et al 2010;Makino et al 2012;Jusoh et al 2014;Duong and Matsumura 2018a, b;Duong et al 2019).…”
Section: Wood Propertiessupporting
confidence: 82%
“…A previous study found a positive correlation between wood density and compressive strength in A. mangium (Makino et al 2012) and A. auriculiformis (Chowdhury et al 2009). In addition, wood density has also been found to be correlated with the MOE and MOR in M. azedarach (Duong and Matsumura 2018a) and Uganda timber species (Zziwa et al 2010). Another study found a high positive correlation between the MOE and MOR (r 0.81) in M. azedarach (Duong and Matsumura 2018a).…”
Section: Relationships Between Air-dry Density and Wood Propertiesmentioning
confidence: 96%
“…Where:F12 = the modulus of rupture at 12% moisture content, W = the moisture content at the time of testing, Fw = the modulus of rupture at the moisture content at the time of testing, 𝛼 = the correction factor for moisture content. 𝛼 was adapted from [10] as 0.04.…”
Section: 𝐹 12 = 𝐹 𝑤 (1 + 𝛼(𝑊 − 12)mentioning
confidence: 99%
“…Additionally, they had even less confidence in other species of wood used for construction in Uganda. While there exists limited information on the strength of these local wood species (Zziwa, Ziraba, & Mwakali, 2010), there were not enough references available to give the engineers great confidence in their assumptions. EMI's desire to increase confidence in material strengths they use for design prompted a collaboration opportunity with a U.S. academic institution for the limited testing of a variety of wood species.…”
Section: Materials Testing -A Collaborative Examplementioning
confidence: 99%
“…The overall goal of the study was to test Ugandan wood samples in general accordance with ASTM procedures to derive strength values in bending, compression, and direct shear. The collaborators selected four wood species based on their use in Ugandan construction, and because they had been included in a study published in the International Wood Products Journal (Zziwa, Ziraba, & Mwakali, 2010). Testing gave structural engineers using these materials another data point with which to compare the reasonableness of their design assumptions.…”
Section: Materials Testing Independent Studymentioning
confidence: 99%